Efficacy of downhill running training for improving muscular and aerobic performances - Toyomura, J.; Mori, H.; Tayashiki, K.; Yamamoto, M.; Kanehisa, H.; Maeo, S. (Applied Physiology, Nutrition, and Metabolism, 2018)
This study investigated effects of downhill (DR) versus level (LR) running training on various muscular and aerobic performances. Eighteen healthy young males conducted either DR (DR group (DRG), n = 10: -10% slope) or LR (LR group (LRG), n = 8) training at a target heart rate (HR) associated with lactate threshold (LT) for 20 min/session, 3 sessions/week, for 5 weeks. Before and after the interventions, the following variables were measured: knee extension torque (-150, -30, 0, 30, 150°·s-1), leg extension power (simultaneous hip and knee extension: 0.8 m·s-1), squat and countermovement jump height, rebound jump index (jump height·contact time-1), 20-m linear sprint and change-of-direction (Pro-agility and V-cut tests) time, and aerobic capacity (maximal oxygen uptake, energy cost at LT, and velocity at maximal oxygen uptake and LT) on a level surface. Throughout the training sessions, HR during running did not differ between the groups (DRG: 77.7% ± 4.6% vs LRG: 76.4% ± 4.6% of maximal HR; average across all sessions), while velocity was significantly higher for DRG (14.5 ± 1.1 vs 12.0 ± 1.9 km/h). After the training, DRG significantly improved knee extension torque at all angular velocities (9%-24%) and change-of-direction time for both tests (2%-3%), with no changes in other parameters. LRG significantly improved maximal oxygen uptake (5%), energy cost at LT (3%), and velocity at maximal oxygen uptake (7%), without changes in others. These results suggest that DR training has a greater potential to improve the knee extension strength and change-of-direction ability, but has little effect on the aerobic capacity, compared with HR-matched LR training.